Peroxisome proliferator-activated receptorα/γ agonist pioglitazone for rescuing relapsed or refractory neoplasias by unlocking phenotypic plasticity - Harrer, Dennis Christoph; Lüke, Florian; Pukrop, Tobias; Ghibelli, Lina; Gerner, Christopher; Reichle, Albrecht; Heudobler, Daniel (Frontiers in Oncology, 2024)
A series of seven clinical trials on relapsed or refractory (r/r) metastatic neoplasias followed the question: Are networks of ligand-receptor cross-talks that support tumor-specific cancer hallmarks, druggable with tumor tissue editing approaches therapeutically exploiting tumor plasticity? Differential recombinations of pioglitazone, a dual peroxisome-proliferator activated receptorα/γ (PPARα/γ) agonist, with transcriptional modulators, i.e., all-trans retinoic acid, interferon-α, or dexamethasone plus metronomic low-dose chemotherapy (MCT) or epigenetic modeling with azacitidine plus/minus cyclooxygenase-2 inhibition initiated tumor-specific reprogramming of cancer hallmarks, as exemplified by inflammation control in r/r melanoma, renal clear cell carcinoma (RCCC), Hodgkin's lymphoma (HL) and multisystem Langerhans cell histiocytosis (mLCH) or differentiation induction in non-promyelocytic acute myeloid leukemia (non-PML AML). Pioglitazone, integrated in differentially designed editing schedules, facilitated induction of tumor cell death as indicated by complete remission (CR) in r/r non-PML AML, continuous CR in r/r RCCC, mLCH, and in HL by addition of everolimus, or long-term disease control in melanoma by efficaciously controlling metastasis, post-therapy cancer repopulation and acquired cell-resistance and genetic/molecular-genetic tumor cell heterogeneity (M-CRAC). PPARα/γ agonists provided tumor-type agnostic biomodulatory efficacy across different histologic neoplasias. Tissue editing techniques disclose that wide-ranging functions of PPARα/γ agonists may be on-topic focused for differentially unlocking tumor phenotypes. Low-dose MCT facilitates targeted reprogramming of cancer hallmarks with transcriptional modulators, induction of tumor cell death, M-CRAC control and editing of non-oncogene addiction. Thus, pioglitazone, integrated in tumor tissue editing protocols, is an important biomodulatory drug for addressing urgent therapeutic problems, such as M-CRAC in relapsed or refractory tumor disease.